2010
DOI: 10.1242/dev.046789
|View full text |Cite
|
Sign up to set email alerts
|

Genomic cis-regulatory networks in the early Ciona intestinalis embryo

Abstract: SUMMARYPrecise spatiotemporal gene expression during animal development is achieved through gene regulatory networks, in which sequence-specific transcription factors (TFs) bind to cis-regulatory elements of target genes. Although numerous cis-regulatory elements have been identified in a variety of systems, their global architecture in the gene networks that regulate animal development is not well understood. Here, we determined the structure of the core networks at the cis-regulatory level in early embryos o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(119 citation statements)
references
References 57 publications
6
113
0
Order By: Relevance
“…Foxa.a, Zic-r.b and Fgf signaling combinatorially activate Brachyury at the 44-cell stage (Imai et al, 2002a(Imai et al, , 2006Yagi et al, 2004;Yasuo and Hudson, 2007). Brachyury encodes a key transcription factor for specifying the notochord, and activates notochord-specific genes directly and indirectly (Chiba et al, 2009;Hotta et al, 2000;Katikala et al, 2013;Kubo et al, 2010;Takahashi et al, 1999). Indeed, in another ascidian species, Halocynthia roretzi, overlapping expression of Foxa and ZicN (an ortholog of Zic-r.b) and activation of Ets by Fgf signaling have been reported to be required for Brachyury expression (Kumano et al, 2006;Matsumoto et al, 2007;Miya and Nishida, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Foxa.a, Zic-r.b and Fgf signaling combinatorially activate Brachyury at the 44-cell stage (Imai et al, 2002a(Imai et al, , 2006Yagi et al, 2004;Yasuo and Hudson, 2007). Brachyury encodes a key transcription factor for specifying the notochord, and activates notochord-specific genes directly and indirectly (Chiba et al, 2009;Hotta et al, 2000;Katikala et al, 2013;Kubo et al, 2010;Takahashi et al, 1999). Indeed, in another ascidian species, Halocynthia roretzi, overlapping expression of Foxa and ZicN (an ortholog of Zic-r.b) and activation of Ets by Fgf signaling have been reported to be required for Brachyury expression (Kumano et al, 2006;Matsumoto et al, 2007;Miya and Nishida, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Ci-Sall-a was too transient to be assessed in either mutant background or by PCR methods (data not shown); however, this gene has been previously indicated as a putative Ci-Bra early target, based upon the occupancy of its genomic locus by Ci-Bra in early embryos (Kubo et al, 2010). The early occupancy of the Ci-Sall-a locus by Ci-Bra is consistent with our detection of Ci-Sall-a in notochord precursors starting from the 64-cell stage.…”
Section: Hierarchical Relationships Between Newly Identified Notochormentioning
confidence: 96%
“…The upstream regulatory cascade leading to Ci-Bra expression is well characterized Imai et al, 2006;Matsumoto et al, 2007), and at least 50 Ciona genes have been found to be controlled by Ci-Bra (Di Takahashi et al, 1999;Hotta et al, 2000;Oda-Ishii and Di Gregorio, 2007;Hotta et al, 2008;Kugler et al, 2008). A surprisingly low number of transcription factors was included within this first set of transcriptional targets; however, this number has been sharply increased by recent wholegenome studies of the in vivo occupancy of chromatin by Ci-Bra in early Ciona embryos (Kubo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The genome browser screen-shot in Figure 2A shows the upstream region of the KH transcript model for Ci-MYT (first three exons, in orange, and two introns are visible). Different genome browser tracks annotate functional genome data predicted for this region, such as chromatin immunoprecipitation (ChIP) data 14 (here shown for ZicL, Ci-zinc finger of the cerebellum L), sequence conservation between two related Ciona species 15,24 or nucleosome occupancy 16,17 (from top to bottom in Figure 2A). Generally, exonic protein coding regions are highly conserved (alignment track in Figure 2A).…”
Section: Electroporation For Efficient Gene Functional and Enhancer Smentioning
confidence: 99%
“…Two of these are predicted to be nucleosome free according to a sequence based algorithm 16,17 (red frames in Figure 2A) suggesting accessibility to transcription factors. Indeed, Chip-on-ChIP signals 14 for Ci-ZicL transcription factor binding (green bars in Figure 2A) are enriched in these two conserved regions. Furthermore, using an interface 25 that searches for potential transcription factor binding sites, we identified ZIC sites located within the genome sequences marked by Ci-ZicL ChIP clusters (orange arrows and sequences with underlined ZIC-core, Figure 2A).…”
Section: Electroporation For Efficient Gene Functional and Enhancer Smentioning
confidence: 99%